RESPON PETANI JAGUNG HIBRIDA TERHADAP KEBIJAKAN HARGA PEMBELIAN PEMERINTAH (HPP) JAGUNG DI KABUPATEN KONAWE - Muhammad Halim; La Rianda Baka; Weka Gusmiarty Abdullah (Jurnal Sosio Agribisnis, 2019)
The development of hybrid corn is a national program in order to achieve the target of corn self-sufficiency. One of the government supports is the issuance of the Government Purchase Price Policy (HPP) through the Minister of Trade Regulation Number 27 / M-DAG/PER / 5/2017 concerning Reference Price for Purchasing Corn. This HPP policy aims to maintain corn availability, price stability and certainty so that the price of corn at the farm level does not fall when the harvest is overflowing. This study was conducted in Konawe District, which is one of the areas of hybrid corn development in Southeast Sulawesi. The aim was to determine the response of hybrid corn farmers to the Government Purchase Price (HPP) policy in Konawe District. The result is the response of hybrid corn farmers to the Government Purchasing Price (HPP) policy in corn in Konawe. Regency is less than or equal to 50% which has a high response because farmers are still uncertain about the certainty of Bulog's purchase of corn and farmers prefer to sell their crops to the farm collectors who provide convenience to corn farmers include not applying water content requirements and purchases made directly to farmers.Keywords: response; price policy; corn